A simple levitated-drop tensiometer - Arcenegui-Troya, J; Belman-Martínez, A; Castrejón-Pita, AA; Castrejón-Pita, JR (AIP Publishing, 2019)
A reliable, simple, and affordable liquid tensiometer is presented in this paper. The instrument consists of 72 ultrasonic transmitters in a tractor beam configuration that levitates small liquid samples (droplets) in air. Under operation, the instrument imparts a pressure instability that causes the droplet to vibrate while still levitating. Droplet oscillations are then detected by a photodiode, and the signal is recorded by an oscilloscope. The frequency of these oscillations is obtained and then used to obtain the effective surface tension of the sample. The instrument operates at the millisecond scale time (t < 12.5 ms), with very small liquid volumes (∼0.5 μl), and the sample is recoverable after testing. The instrument has been experimentally validated with acetone, ethanol, Fluorinert FC-40, water, and whole milk.